Wages : a Means of Testing Their Adequacy - Leeds, Morris Evans; Balderston, C. Canby (Philadelphia, Pa. : University of Pennsylvania Press, 2017)
This book is a volume in the Penn Press Anniversary Collection. To mark its 125th anniversary in 2015, the University of Pennsylvania Press rereleased more than 1,100 titles from Penn Press's distinguished backlist from 1899-1999 that had fallen out of print. Spanning an entire century, the Anniversary Collection offers peer-reviewed scholarship in a wide range of subject areas.
Frontmatter -- Acknowledgments -- Contents -- Introduction -- Chapter I. Changing Conceptions of Wage Levels -- Chapter II. The Relation of the Size of the Family to Age and Service -- Chapter III. The Cost-of-Living Budgets Graduated According to the Size of Family and Related to Age and Service -- Chapter IV. The Uses of Graduated Maintenance Budgets -- Chapter V. Summary -- Appendix A. Method of Computing the Maintenance Budgets -- Appendix B. Some Notes on the Difficulties of Determining the "Market Rate" -- Bibliography -- Index
In English.
Online resource; title from PDF title page (publisher's Web site, viewed Jan. 23, 2017).
JSTOR
Keywords: Wages -- United States; Cost and standard of living -- United States; Working class -- United States; Home economics -- Accounting; Coût et niveau de la vie -- États-Unis.; Travailleurs -- États-Unis.; Budgets familiaux; BUSINESS & ECONOMICS -- Econometrics; Cost and standard of living; Home economics -- Accounting; Wages; Working class; United States; Business; Economics